The effects of porcine reproductive and respiratory syndrome (PRRS) vaccination on postweaning growth performance - S D Pretzer; K M Claussen; J R Bergstrom; Steven C Henry; R Phillips; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
We evaluated the effects of a modified-live virus vaccine for PRRS virus on nursery growth performance. The pigs used in this study were obtained from a herd with substandard nursery growth performance attributed to PRRS virus infection. We failed to detect the presence of active circulating field strain virus in either the controls or vaccinated pigs. However, we did detect a strain similar to the vaccine virus strain on d 34 after weaning in the vaccinated pigs. The vaccinated pigs had poorer growth performance from d 7 to 14 after vaccination and were lighter in weight for the remainder of the experiment. Vaccinating uninfected pigs with a modified-live vaccine (RespPRRS TM) has a cost in growth performance. Therefore, determining if virus is circulating within the nursery population is necessary before vaccinating.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Porcine reproductive and respiratory syndrome; Nursery pigs; Vaccination